PRINSIP DAN KONSEP MANAJEMEN SYARIAH - Moza Indah Febryani; Dewi Sartika; Sasqiasalsabilla; Raditio; Aldy Saputra; Muhammad Ghiffran Arrony; Putri rizki (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
This research aims to analyze the principles and concepts of Sharia management as a framework for organizational governance based on Islamic values. The main focus of the research is to examine the integration of the values of monotheism, justice, trustworthiness, consultation, and public interest in managerial practices and to compare them with conventional management. This research uses a qualitative literature study method, with data sources from journals from the last five years and books from the last ten years that are relevant. The research results show that the concept of sharia management emphasizes the management of organizations based on Islamic ethical principles, which are reflected in all managerial functions such as planning, organizing, directing, and controlling. These findings affirm that the implementation of sharia management strengthens the organization's orientation towards ethics, transparency, and social responsibility, as well as enhances stakeholder trust and the organization's reputation. The Sharia management model is considered adaptive and sustainable, in line with the needs of modern organizational governance.